Effects of fastigial nucleus electrostimulation on cardiac nerve regeneration, neurotransmitter release, and malignant arrhythmia inducibility in a post‐infarction rat model. (18th November 2021) - Su, Mouxiao; Luo, Zhi; Yu, Jiang; Zhang, Runfeng; Wang, Jisheng; Huang, Changquan; Li, Wensong; Yuan, Wei; Zhang, Heng; Cai, Guocai; Shen, Songlin
Abstract: The reduced density of cardiac autonomic nerves plays an important role in malignant arrhythmia after myocardial infarction (MI). Previous studies have shown that there is an interaction between the brain and the heart, and fastigial nucleus electrostimulation (FNS) promotes central nerve regeneration. Whether and how it can promote cardiac nerve regeneration after MI and the underlying mechanisms remain unknown. This study investigated whether FNS promotes cardiac nerve regeneration and reduces malignant arrhythmia inducibility in a post‐infarction rat model. Ninety‐eight Wistar rats were randomly assigned to Sham control, MI (left anterior descending coronary artery ligation without FNS), FNS (MI plus FNS), and FNL (fastigial nucleus lesion plus FNS plus MI) groups. The frequency of malignant arrhythmia was significantly lower in the FNS group than in the MI and FNL groups. The density of cardiac autonomic nerves was less in the MI group than in the Sham group, which was promoted by FNS. The nerve growth factor (NGF) mRNA expression was downregulated in the MI group compared to the Sham group, which was significantly enhanced by FNS. The expression levels of norepinephrine (NE) and acetylcholine (ACh) were higher and lower respectively in the MI and FNL groups than in the Sham group. After FNS, NE concentration was reduced and Ach level was elevated compared to the MI group. These data suggested that FNS promoted the regeneration of cardiac autonomic nerves and reduced the incidence of malignant arrhythmias in MI rat model. The mechanisms might involve up‐regulation of NGF mRNA expression, decrease of NE release and increase of ACh release. Abstract : The cerebella fastigial nucleus electrostimulation (FNS) may have protective effects against ischaemic heart damage through an inherent neural pathway. FNS can reduce the incidence of malignant arrhythmia after acute myocardial infarction (AMI) by enhancing the expression of nerve growth factor, promoting the regeneration of cardiac autonomic nerves, and regulating the release of neurotransmitters.